Differential Distribution of Trypanosoma vivax and Trypanosoma theileri in Cattle from Distinct Agroecological Regions of Central Argentina - Maria Celeste Facelli Fernández; Johann Barolin; Martin Allassia; Javier Hernan Gonzalez; Pablo Martin Beldomenico; Lucas Daniel Monje (Parasitologia)
Bovine trypanosomiasis, caused by Trypanosoma vivax, affects livestock productivity and is increasingly being reported in South America. This study aimed to detect and characterize Trypanosoma spp. infections, with a focus on T. vivax, in cattle from two distinct agroecological regions of central Argentina: a dairy-producing plain, located in the Espinal ecoregion, and a riparian zone, dedicated to beef production, located in the Delta and Islands of Paraná ecoregion. A total of 220 blood samples were collected from nine cattle farms and analyzed using real-time PCR, melting curve analysis, and the sequencing of 18S rRNA gene fragments. Trypanosoma vivax was detected at low prevalence (2.73%), exclusively in dairy cattle. In contrast, the prevalence of Trypanosoma theileri was much higher (10.91%), and it was found mainly in beef cattle from the riparian region. Phylogenetic analyses confirmed the species identity in all sequenced samples. No trypanosomes were observed by microscopy, and none of the animals showed clinical signs. The results indicate a differential distribution of T. vivax and T. theileri between regions and production systems. Although the study initially focused on T. vivax, the detection of T. theileri highlights the need to consider multiple Trypanosoma species in epidemiological surveys. This study contributes new data on the occurrence of bovine trypanosomes in central Argentina under extensive and semi-intensive management systems.